Pressões Isomórficas e Padrões Contábeis para o Reconhecimento de Receitas: Um Paradoxo nos Escritórios de Contabilidade - Colla, Pâmila Eduarda Balsan (2021)
Organizations are inserted in the social environment through their relationships. Faced with these challenges, they suffer internal and external pressures, this so-called institutional isomorphism. It is intended that this scenario can reach the process of recognizing revenue from contracts with clients since such assignment of the organizational field represents the vital fluid for the continuity of operations and meeting the expectations and information needs of agents. Therefore, in view of this gap, this dissertation aims to understand the role of isomorphic pressures in the face of the adoption of criteria for the recognition of revenues carried out by accounting firms. To this end, research was carried out which tests six propositions, based on a descriptive design, with a qualitative approach, and with a survey typology. Research participants comprise internal and external agents. Regarding internal agents, they are accounting professionals in offices, while external agents represent a financial institution, the audit, the professional body, and the Federal Revenue Service. In view of the participants' search to constitute the present research, it was possible to gather eight internal and external agents that throughout this investigation print their perceptions regarding the constructions that make up the research, inscribed in the role of isomorphic pressures in the face of the adoption of criteria for the recognition of revenues carried out by accounting firms. Content analysis was used, from the transcripts of the interviews of the internal agents it was possible to elaborate six categories of analysis included in i) Types of the company that make up the client portfolio of the accounting office; ii) Revenue and Business Activities of the Clients of the Accounting Office; iii) Procedure for the Recognition of Revenue; iv) Generating Fact for the Recognition of Revenue; v) Factors linked to the Revenue Recognition Criteria; and iv) Guidance and alignment with the customer for the revenue recognition process. Starting from the interviews with external agents, it was possible to elaborate four, namely: i) Expectation for the Recognition of Revenue; ii) Criteria Observed in the Recognition of Revenue; iii) Pressure exerted on the accounting practice of revenue recognition; and iv) Information provided to external users on the recognition of revenues and the representation of the economic essence of the organization. It is worth noting that the analysis and data collection procedures respond to the field of investigation. In this way, intermediation between the disciplinary field and the dispositions in terms of methods and techniques is visualized, facts that allow testing the research proposals. From the evidence, it is possible to conclude that the criteria for the recognition of revenue are based on a fiscal perspective, adopted from the multiple isomorphic pressures suffered and which are mostly coercive. As these practices are adopted from coercive pressures and that yielding to this accounting dynamic is seen as acceptable by the different agents, including the guardian of good accounting practices - represented here by the CRC - it is possible to say that the accounting offices reach organizational legitimacy when aligning and meeting the expectations of these different agents.